Green Synthesis of Gold Nanoparticles Mediated by Garcinia Fruits andTheir Biological Applications - Azazahemad A Kureshi; Hiral M Vaghela; Satyanshu Kumar; Raghuraj Singh; Premlata Kumari (Tabriz University of Medical Sciences, 2021)
Background: Green synthesis of gold nanoparticles (AuNPs) using medicinal plant extract is an emerging area of research due to their applicability in nanomedicines. Methods: In this study, aqueous extracts prepared from fruit-pericarps of two Garcinia species, G. indica (GI) and G. cambogia (GC) fruits which are important medicinally and commercially have been utilized for the synthesis of AuNPs. Various analytical techniques were utilized to characterize the synthesized AuNPs. The synthesized AuNPs were investigated for their biological properties such as antioxidant activity using the (2,2-diphenyl-1-picrylhydrazyl) DPPH model, cytotoxicity against MCF-7 (breast) cancer cell line, and antibacterial activity against two bacterial strains viz. B. subtilis and E. coli. Results: The absorption peak of the AuNPs is observed at 541 nm using UV-Visible spectroscopy. The high resolution - scanning electron microscopy images showed spherical with a triangular shape AuNPs and their average sizes were ranging from 2 - 10 nm and it was found to be in good agreement with the particle size of 8 - 11 nm determined using X-ray diffraction analysis. Fourier-transform infrared spectroscopy revealed that water-soluble biomolecules from the aqueous extracts of the Garcinia species played a crucial role in the formation of AuNPs. The synthesized AuNPs exhibited considerable cytotoxicity with IC50 values 34.55 µg/ml (GI) and 35.69 µg/ml (GC) against the MCF-7 cancer cell line. Furthermore, synthesized AuNPs also demonstrated significant antioxidant and antibacterial properties comparable to the standards used. Conclusion: AuNPs have been synthesized using a simple green approach. The synthesized AuNPs demonstrated promising cytotoxicity, antioxidant, and antibacterial properties.